Effective treatment of aggressive fibromatosis with celecoxib guided by genetic testing. Issue 10 (3rd October 2017) - Yang, Shanshan; Wang, Xufu; Jiang, Haiping; Wang, Yongjie; Li, Zhuokun; Lu, Haijun
ABSTRACT: Aggressive fibromatosis (AF) or desmoid tumors is an aggressive fibroblastic proliferation which is locally invasive but can not metastasize. The treatment of AF is challenging. Surgery was the main treatment modality for AF in the past, other strategies including radiotherapy, systemic therapies and wait-and-see policy. The use of non-steroidal anti-inflammatory drugs (NSAIDs) and targeted therapies has demonstrated good results. In the case report, a 39-year-old man presented with progressive chest wall pain. Computed tomography (CT) showed an approximately 46× 13 mm soft-tissue mass between the inside of the fifth and sixth rib on the right side. The entire mass was excised and an AF was confirmed based on histopathology. Four months after surgery, magnetic resonance imaging (MRI) showed a soft-tissue mass in surgical areas and biopsy confirmed local recurrence. Therefore, Tomotherapy was administered. However, two months later, an (18)F-fluorodeoxyglucose (FDG) Positron Emission Tomography combined with CT (PET-CT) revealed the presence of an FDG-avid mass in the area of local recurrence. Genetic testing reported the presence of a p.T41A mutations on the CTNNB1 gene, which predicted that he is sensitive to the COX-2 inhibitor celecoxib. The tumor regressed rapidly after the application of celecoxib. Within the 20-month follow-up period, the patient showed remarkable regression without any signs and symptoms. Our case report provides further evidence for the efficacy of celecoxib in AF with CTNNB1 gene mutations. To our knowledge, this is the first report of AF treated with celecoxib under the guidance of the genetic testing. However, further studies are required.